MAXIMIZING TELEGRAM APPLICATION FOR TEACHING READING - Fhesti Mayang Sari (Universitas Ahmad Dahlan)
Curriculum, syllabus and technology are the educational terms with their certain components and importance. They are also could be said as the guidelines for gaining educational goals. The use of mobile phone has become an essential part of nowadays students’ lives in the world. That is why the role of technology is also could not be separated with the content of the syllabus. This article aims to discuss the use of technology−in the form of Telegram as one of the mobile phone application−by inserting it in the syllabus related to the teaching and learning English especially for teaching reading. At the end of the discussion, it is found that those variables are influencing each other. Curriculum is as the reference of syllabus whereas syllabus is as the implementation of curriculum and technology supports them. A teacher could use Telegram by setting up a certain group discussion in a single classroom to maximize the learning process. When the teachers provided a Telegram group discussion with its interesting and appropriate context for students, it is possible to make students curious. When the students’ curiosity occured, the habitual process of reading begins. This could be one of a problem solving of students’ laziness of going to the school library. By the time the students have read several books or articles or another media that they like, the teachers could encourage them to share it with their classmates in some ways by maximizing their Telegram group.